2002
DOI: 10.1021/jp013808u
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics in Ionic Liquids as Studied by Pulse Radiolysis:  Redox Reactions in the Solvents Methyltributylammonium Bis(trifluoromethylsulfonyl)imide and N-Butylpyridinium Tetrafluoroborate

Abstract: Rate constants for several reduction and oxidation reactions were determined by pulse radiolysis in three ionic liquids and compared with rate constants in other solvents. Radiolysis of the ionic liquids methyltributylammonium bis(trifluoromethylsulfonyl)imide (R4NNTf2), N-butylpyridinium tetrafluoroborate (BuPyBF4), and N-butyl-4-methylpyridinium hexafluorophosphate (BuPicPF6) leads to formation of solvated electrons and organic radicals. In R4NNTf2 the solvated electrons do not react rapidly with the solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 23 publications
3
116
2
Order By: Relevance
“…Remaining unreacted alkyl bromide was evaporated from the resultant solutions. When preparing C n MIMBF 4 , [45,46] C n MIMBr was mixed with > 10 % excess NH 4 BF 4 in acetonitrile at r.t. and stirred for at least 4 days. The white precipitates of unreacted NH 4 BF 4 and NH 4 Br (a byproduct) were filtered and acetonitrile was completely removed from the resultant liquids.…”
Section: Methodsmentioning
confidence: 99%
“…Remaining unreacted alkyl bromide was evaporated from the resultant solutions. When preparing C n MIMBF 4 , [45,46] C n MIMBr was mixed with > 10 % excess NH 4 BF 4 in acetonitrile at r.t. and stirred for at least 4 days. The white precipitates of unreacted NH 4 BF 4 and NH 4 Br (a byproduct) were filtered and acetonitrile was completely removed from the resultant liquids.…”
Section: Methodsmentioning
confidence: 99%
“…Several pulse radiolysis studies on ionic liquids (Behar et al, 2001;Behar et al, 2002;Grodkowski and Neta, 2002a-c;Wishart and Neta, 2003;Grodkowski et al, 2003;Wishart et al, 2005;Kato, et al, 2007;Takahashi et al, 2007;Kimura et al, 2007) have been reported. The researches indicate that, for the imidazolium ionic liquids, dry electrons produced by ionization before full solvation are rapidly scavenged by the solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…As to the chalcones (Entries 1-3, 6-8) with the internal C=C bonds, the epoxides were the only products, implicating the facial access of the substrate to oxomanganese(V) porphyrin domain [31]. And due to the bulky hindrance, the conversions of the chalcones were relatively lower due to the unfavorable accessibility of C=C site to the manganese porphrin center.…”
Section: Comparison Of the Catalytic Performancementioning
confidence: 99%